REACTIVE AND PROACTIVE AGGRESSION IN ADOLESCENT MALES: Examining Differential Outcomes 10 Years Later in Early Adulthood - Fite, Paula J. (2009)
There is limited knowledge about the unique relations between adolescent reactive and proactive aggression and later psychosocial adjustment in early adulthood. Accordingly, this study prospectively examined associations between adolescent (mean age = 16) reactive and proactive aggression and psychopathic features, antisocial behavior, negative emotionality, and substance use measured 10 years later in early adulthood (mean age = 26). Study questions were examined in a longitudinal sample of 335 adolescent males. Path analyses indicate that after controlling for the stability of the outcome and the overlap between the two subtypes of aggression, reactive aggression is uniquely associated with negative emotionality, specifically anxiety, in adulthood. In contrast, proactive aggression is uniquely associated with measures of adult psychopathic features and antisocial behavior in adulthood. Both reactive and proactive aggression uniquely predicted substance use in adulthood, but the substances varied by subtype of aggression. Implications for findings are discussed.